2012
DOI: 10.2131/jts.37.439
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of trichloroethylene and tetrachloroethylene on type I allergic responses in mice

Abstract: -Trichloroethylene (TCE) and tetrachloroethylene (perchloroethylene; PCE) are commonly identified as environmental contaminants of groundwater. Previously, we investigated the enhancing effects of TCE and PCE on antigen-induced histamine release and inflammatory mediator production in rat mast cells. In this study, to examine the potential effect of TCE and PCE on antigen-induced histamine release from mouse mast cells, mouse bone marrow-derived mast cells (BMMC) were sensitized with anti-dinitrophenol (DNP) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Treatment with tetrachloroethylene also increased mRNA expression of IL-4 (p<0.05) and TNF-α (p>0.05) as well as the production of these mediators (p<0.05 for both) in RBL-2H3 cells. A dosedependent increase in antigen-induced histamine release from mouse bone marrow cells treated with tetrachloroethylene was reported in another study from this laboratory (Seo et al 2012). These data suggest possible mechanisms for tetrachloroethylene-induced perturbation of the immune response to allergens, and exacerbation of inflammation.…”
Section: Renal Effectssupporting
confidence: 74%
See 2 more Smart Citations
“…Treatment with tetrachloroethylene also increased mRNA expression of IL-4 (p<0.05) and TNF-α (p>0.05) as well as the production of these mediators (p<0.05 for both) in RBL-2H3 cells. A dosedependent increase in antigen-induced histamine release from mouse bone marrow cells treated with tetrachloroethylene was reported in another study from this laboratory (Seo et al 2012). These data suggest possible mechanisms for tetrachloroethylene-induced perturbation of the immune response to allergens, and exacerbation of inflammation.…”
Section: Renal Effectssupporting
confidence: 74%
“…Enhanced antigen-stimulated allergic responses have been demonstrated following small oral doses of tetrachloroethylene in both rats (Seo et al 2008a) and mice (Seo et al 2012). In addition, rats exposed to tetrachloroethylene displayed enhanced inflammatory responses (Seo et al 2008a).…”
Section: Immunological and Lymphoreticular Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other research of THS, many researchers found that T cell-mediated type IV hypersensitivity could not fully explain the pathogenesis of THS (Chiu et al, 2013; Seo et al, 2012; Wang et al, 2014). In a cross-sectional study of occupational TCE exposure, exposed workers had significant declines in peripheral blood cell counts, total lymphocytes, and some lymphocyte subsets, including B cells and CD4+ T cells, as well as plasma markers of B cell activation compared with unexposed factory workers (Hosgood, 2012; Lan et al, 2010).…”
Section: Humoral Immunity Of Tcementioning
confidence: 99%
“…Chinese research found that TCE intake via drinking water can upregulate the expression of IFN-γ and IL-4, which may promote Th1 and Th2 cell immune response, and when Th2 cell increases significantly, the proportion of Th1/Th2 decreases (Li et al, 2014). Th1/Th2 cytokine imbalance induced by TCE ingestion will promote a type I hypersensitivity reaction (Seo et al, 2012). However, serum immunoglobulin E (IgE) levels were not significantly different between TCE-exposed and -unexposed workers after adjustments for age, gender, alcohol consumption, and so on.…”
Section: Cellular Immunity Of Tcementioning
confidence: 99%